Long-term weight gain after initiating combination antiretroviral therapy in treatment-naïve Asian people living with human immunodeficiency virus. (September 2021) - Ando, Naokatsu; Nishijima, Takeshi; Mizushima, Daisuke; Inaba, Yosuke; Kawasaki, Yohei; Kikuchi, Yoshimi; Oka, Shinichi; Gatanaga, Hiroyuki
Highlights: Body weight increases among Asian people living with human immunodeficiency virus following the initiation of antiretroviral therapy (ART). Long-term weight gain following ART initiation depends on drug combination The combination of dolutegravir plus tenofovir alafenamide (TAF)/emtricitabine is associated with the greatest weight gain. TAF-containing regimens are associated with the greatest weight gain. ABSTRACT: Objective: To investigate changes in weight following the initiation of antiretroviral therapy in treatment-naïve Asian people living with human immunodeficiency virus (PLWH). Methods: This retrospective observational study evaluated adult treatment-naïve Asian PLWH who started antiretroviral therapy based on an integrase strand transfer inhibitor, a protease inhibitor or a non-nucleoside reverse transcriptase inhibitor at the AIDS Clinical Centre, Tokyo between January 2005 and February 2019. Patients were followed-up until October 2019. Multi-variate linear mixed-effects models were used to generate marginal predictions of weight over time. Predicted weight was reported at 3-month intervals until censoring or for 5 years after treatment initiation. Results: Five years after treatment initiation, average weight gain in PLWH who started on dolutegravir-, darunavir- and elvitegravir-based treatment was 5.3 kg, 4.1 kg and 4.6 kg, respectively, while those who started on raltegravir-, lopinavir- and atazanavir-based treatment gained an average of 1.9 kg, 2.1 kg and 2.3 kg, respectively. Average weight gain in PLWH who started treatment with the backbone drugs, tenofovir alafenamide, abacavir and tenofovir disproxil fumarateb was 4.1 kg, 3.0 kg and 3.0 kg, respectively, and those treated with dolutegravir plus tenofovir alafenamide/emtricitabine gained an average of 6.7 kg. Conclusions: Antiretroviral-therapy-associated weight gain continued to increase for 5 years following treatment initiation. A combination of dolutegravir and tenofovir alafenamide/emtricitabine was associated with the greatest weight gain.